Intramural pregnancy after intrauterine insemination in a nulligravid patient without previous uterine trauma, complicated by idiopathic thrombocytopenic purpura: A case report - Koyo Yamamoto; Tsuyoshi Takiuchi; Kengo Kiso; Saki Ishii; Satoshi Nakagawa; Yasuto Kinose; Michiko Kodama; Yutaka Ueda; Kenjiro Sawada; Takahiro Tsuboyama; Tadashi Kimura (Case Reports in Women's Health)
Intramural pregnancy (IMP) is an extremely rare form of ectopic pregnancy (EP), typically associated with previous uterine trauma, adenomyosis, or assisted reproductive technology (ART), such as embryo transfer (ET). Despite its potentially life-threatening nature, the absence of definitive preoperative diagnostic criteria for IMP complicates its early detection and management, especially in patients without known risk factors. Additionally, management becomes more challenging when there is an elevated risk of hemorrhage. We report the case of a 34-year-old nulligravid woman referred to a tertiary hospital with suspected EP and bilateral ovarian endometriomas following intrauterine insemination. The patient had no history of uterine trauma or ET. Blood tests and ultrasonography supported the diagnosis of EP, and computed tomography suggested peritoneal pregnancy. Upon further investigation, the patient was diagnosed with idiopathic thrombocytopenic purpura, presenting with a platelet count of 30,000/μL. Due to the associated risk of hemorrhage, we proceeded with emergency exploratory laparoscopy after platelet transfusion. Intraoperatively, when an IMP was identified, the procedure was rapidly converted to laparotomy owing to bleeding risk associated with idiopathic thrombocytopenic purpura. The gestational sac covered with the uterine serosa was dissected, and the uterine defect was repaired to preserve fertility. The blood loss was 320 mL. The patient's postoperative recovery was uneventful, and histopathological examination confirmed the diagnosis of IMP. The patient later resumed ART and successfully achieved term pregnancy, leading to a normal vaginal delivery 3 years after the initial surgery. Early diagnosis and appropriate management of IMP are critical to prevent severe intraperitoneal bleeding, while preserving future fertility.